Literatura testimonial de la otra memoria democrática española : republicana, antifascista e internacionalista - Antonio Prado del Santo (Amnis, 2021)
The present draft bill issued by the Spanish State on democratic memory has yet to abolish or reinterpret the Amnesty Law of 1977. As a consequence, this law continues to act as a full stop law, despite the disapproval of the United Nations. By leaving Francoism unpunished while pretending to honour its victims, the Kingdom reveals that its memory has, precisely, a democratic limit : the Republic. In contrast with this equidistant, monarchic, and national account of the war of Spain and its consequences, I point out the value of another democratic memory that competes for legitimacy : the Republican, antifascist, and internationalist one. With this in mind, I offer a Benjaminian reading of the Republican testimonial literature that looks back on the geopolitical connection of the War in Spain with the Second World War : their retreat to France, their stay in the French camps and their participation in the French Resistance